2020
DOI: 10.3389/fcell.2020.00474
|View full text |Cite
|
Sign up to set email alerts
|

The Role of RNA Splicing Factors in Cancer: Regulation of Viral and Human Gene Expression in Human Papillomavirus-Related Cervical Cancer

Abstract: The spliceosomal complex components, together with the heterogeneous nuclear ribonucleoproteins (hnRNPs) and serine/arginine-rich (SR) proteins, regulate the process of constitutive and alternative splicing, the latter leading to the production of mRNA isoforms coding multiple proteins from a single pre-mRNA molecule. The expression of splicing factors is frequently deregulated in different cancer types causing the generation of oncogenic proteins involved in cancer hallmarks. Cervical cancer is caused by pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 290 publications
(337 reference statements)
3
46
0
Order By: Relevance
“…Cervical cancer, as one of the common human tumors, is one of the most common gynecological malignancies, [1][2][3][4][5]34 which is like other tumors [35][36][37][38][39][40][41] and they threatened seriously to human health as well as cervical cancer, [42][43][44][45][46][47][48] its morbidity and mortality rate are at the forefront of female malignancies. Surgery, radiotherapy and chemotherapy for early cervical cancer have good effects, but in advanced stage, the therapeutic effect of metastatic and recurrent cervical cancer is very limited and the survival rate is low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical cancer, as one of the common human tumors, is one of the most common gynecological malignancies, [1][2][3][4][5]34 which is like other tumors [35][36][37][38][39][40][41] and they threatened seriously to human health as well as cervical cancer, [42][43][44][45][46][47][48] its morbidity and mortality rate are at the forefront of female malignancies. Surgery, radiotherapy and chemotherapy for early cervical cancer have good effects, but in advanced stage, the therapeutic effect of metastatic and recurrent cervical cancer is very limited and the survival rate is low.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is considered to be one of the most common gynecological malignant tumors in the world and highly occurred in developing countries, [1][2][3][4][5] which is a serious threat to women's health. Globally, cervical cancers rank the fourth one among female tumor causes of death and the incidence of cervical cancer ranks the first one among female genital malignancies in China.…”
Section: Introductionmentioning
confidence: 99%
“…During the viral replicative cycle, polycistronic RNAs are transcribed, which undergo alternative splicing through differential use of splicing sites located in the viral genome [41]. Thus, mRNAs expressed from the early promoter located at p97 (HPV16) are translated for expressing E6, E6*I, E7, E1, E2, E8, E4, and E5 proteins [41,61]. Interestingly, it was reported that E6*I transcripts facilitates E7 translation by increasing the space between the E6 stop codon and the E7 start codon [62].…”
Section: Gene Expression Regulationmentioning
confidence: 99%
“…In that case, the effect of the knockdown might reflect the general changes in the expression of the splicing regulators that play roles in our exons' recognition rather than their direct binding to 3 ss. Because we used the cancerous cell line HeLa in our experimental procedures, we had to count with the inherent splicing factors' deregulated expression, which is a common phenomenon in many cancer types [54]. Therefore, even the intrinsic SRSF1 and U2AF35 expression in our cells may differ from non-malignant mammalian tissues.…”
Section: Discussionmentioning
confidence: 99%